2018
DOI: 10.1016/j.rmed.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Systemic vascular dysfunction is associated with emphysema burden in mild COPD

Abstract: Systemic vascular dysfunction is present in the earlier stages of COPD, particularly in patients with greater emphysema burden and low TL. Regardless FEV, patients showing those structural and functional abnormalities might be at higher risk of negative events thereby deserving closer follow-up for early detection of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…Arterial stiffness is a strong predictor of cardiovascular disease [47,48], and emphysema severity based on quantitative computed tomography scans in turn was revealed as the most powerful predictor of arterial stiffness [49]. Moreover, systemic vascular dysfunction seems to already be present in the earlier stages of COPD, and particularly in patients with emphysema, although presenting with a largely preserved FEV1 [50].…”
Section: Coronary Artery Disease In Copdmentioning
confidence: 99%
“…Arterial stiffness is a strong predictor of cardiovascular disease [47,48], and emphysema severity based on quantitative computed tomography scans in turn was revealed as the most powerful predictor of arterial stiffness [49]. Moreover, systemic vascular dysfunction seems to already be present in the earlier stages of COPD, and particularly in patients with emphysema, although presenting with a largely preserved FEV1 [50].…”
Section: Coronary Artery Disease In Copdmentioning
confidence: 99%
“…Hence, 21 studies enrolling 638 patients with COPD and 595 controls were included in this systematic review. From the 21 studies, only 19 studies (with 968 participants) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] were included in the quantitative analysis, since available data for the rest 2 were inadequate [42,43].…”
Section: Search Resultsmentioning
confidence: 99%
“…Of the 21 studies included in this systematic review, 16 studies evaluating endothelial function only via FMD (8 NMD) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], 2 only via VOP [forearm blood flow (FBF) assessment after bradykinin infusion] [23,24], 1 study via FMD and VOP (FBF after a typical post-occlusion reactive hyperemia protocol) [25], 1 study via PAT [26] and 1 study via FMSF [27]. Seven studies included patients with COPD, without overt cardiovascular disease [23, 26, 31-33, 39, 40] and 1 study included patients with COPD and CAD co-existence [25].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, Katz et al reported that in an invasive femoral venous blood study, patients with heart failure had higher oxygen extraction in leg muscles at peak exercise than healthy subjects [51]. Similarly, Zelt et al reported that in patients with mild COPD, there was higher oxygen extraction in forearm muscles performing a continuous isometric handgrip squeeze at 20% of maximal voluntary contraction for 1.5 min compared to age-matched normal subjects [11]. We speculate that (1) the femoral vein and NIRS provide different information, as the former collects both superficial and deep leg veins whereas the latter collects the superficial microcirculation, and (2) all of the previous studies and the present study used different exercise protocols and different methods to calculate HbO 2 , HHb, and TOT, and measured different groups of muscles, and that all of these factors may have caused the difference in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the mechanisms of myopathy, muscle morphology, muscle fiber type distribution and shifting, and muscle metabolism in the locomotor muscles are similar in patients with COPD and CHF [1,9], exercise-induced hypoxemia, if it occurs, is expected to aggravate hypoxic stress in patients with COPD, as the patterns of muscle cytochrome oxidase gene activation are altered in these patients [8]. In addition, hypoxemia may cause an increase in myostatin protein expression, which is related to muscle atrophy [10], and patients with COPD can experience vascular dysfunction with a higher extraction of muscle oxygen during exercise even in the early stage [11]. Therefore, it is not clear whether there are differences in the functions of locomotor and ventilatory muscles between patients with COPD and CHF who have similar daily exercise performance and dyspnea sensation.…”
Section: Introductionmentioning
confidence: 99%